PENINGKATAN PRESTASI BELAJAR KONSEP TAHAP PENCATATAN SIKLUS AKUNTANSI PERUSAHAAN DAGANG MENGGUNAKAN STRATEGI PEMBELAJARAN KOMPETITIF PADA SISWA KELAS XI IPS 1 SMA N 1 KERAMBITAN TAHUN PELAJARAN 2017/2018 - Yusniawati, Gusti Ayu Arry (Widyadari : Jurnal Pendidikan, 2019)
The main problem of this study is the minor low and student achievement to master and understand accounting competencies. Indicators of low minority and learning achievement are indicated by the low response and student participation in learning and the low level of involvement and activity of students in teaching and learning activities. Starting from these problems, a solution is found by conducting Class Action Research through competition learning strategies.         The class action research was conducted in September 2018 in class XI IPS 1 Kerambitan 1 Public Senior High School in the first semester of the 2017/2018 school year with a total of 43 students consisting of 20 male students and 23 female students. This research activity consists of 2 cycles including 4 stages, namely Planning, Action, Observation, and Reflection.         In the first cycle the research tried to add learning strategies that could be more uplifting and interest in learning and could involve students to play an active role with competitive learning strategies with the hope that the results to be achieved can improve learning achievement, namely 75% of students in class XI IPS 1 can achieve a minimum value of 74. In cycle II aims to improve all obstacles and weaknesses found in the first cycle in the hope of achieving higher learning achievement results, namely the average value above 74.         In data collection the researcher used the learning process observation format, daily test / repetition results from the questionnaire and assessment of the process in the competition as well as learning fogs. The results of the study indicate an increase in the value of learning outcomes; this can be observed from the results of the average value of each test (daily test). The average daily repeat value in the initial conditions is 68 - 56% absorption; in Cycle I the average score was 78- 79% absorption, while in the Cycle the average value was 79 - 84% absorption.         Based on the results of this class action research it can be concluded that the Learning Strategy Competition can improve the learning achievement of Accounting for students.